2014
DOI: 10.1007/s00784-014-1358-3
|View full text |Cite
|
Sign up to set email alerts
|

Zoledronate but not denosumab suppresses macrophagic differentiation of THP-1 cells. An aetiologic model of bisphosphonate-related osteonecrosis of the jaw (BRONJ)

Abstract: This is the first real-time study providing evidence for a dose-dependent immunosuppressive effect of zoledronate in contrast to denosumab on local macrophages.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 43 publications
0
16
0
2
Order By: Relevance
“…Several publications have reported that N‐BPs can modulate the differentiation/function of immune cells with consequences on the inflammatory response. Macrophages (Hoefert et al, ) and T‐lymphocytes (Kalyan, Quabius, Wiltfang, Mönig, & Kabelitz, ) appear to be the most commonly‐affected immune cells but an impact on dendritic cells (Bringmann et al, ) and neutrophil granulocytes (Hagelauer, Pabst, Ziebart, Ulbrich, & Walter, ) has also been reported. The fact that patients treated with a combination of N‐BPs and immune modulator drugs such as Adalimumab (Preidl et al, ), Sunitinib (Hoefert & Eufinger, ), and aromatase inhibitors (Kourie et al, ) are evidence of enhanced frequency of BRONJ compared to patients treated simply that enforces the idea that immune modulation by N‐BPs may be implicated in the occurrence of side effects.…”
Section: Future Directions For Controlling the Side Effects Of N‐bpsmentioning
confidence: 99%
“…Several publications have reported that N‐BPs can modulate the differentiation/function of immune cells with consequences on the inflammatory response. Macrophages (Hoefert et al, ) and T‐lymphocytes (Kalyan, Quabius, Wiltfang, Mönig, & Kabelitz, ) appear to be the most commonly‐affected immune cells but an impact on dendritic cells (Bringmann et al, ) and neutrophil granulocytes (Hagelauer, Pabst, Ziebart, Ulbrich, & Walter, ) has also been reported. The fact that patients treated with a combination of N‐BPs and immune modulator drugs such as Adalimumab (Preidl et al, ), Sunitinib (Hoefert & Eufinger, ), and aromatase inhibitors (Kourie et al, ) are evidence of enhanced frequency of BRONJ compared to patients treated simply that enforces the idea that immune modulation by N‐BPs may be implicated in the occurrence of side effects.…”
Section: Future Directions For Controlling the Side Effects Of N‐bpsmentioning
confidence: 99%
“…In bisphosphonate-treated rodent models, tooth extraction is associated with the development of osteonecrosis in the jawbone and prolonged chronic inflammation in oral barrier tissue (30,31). It has been indicated that bisphosphonates can be taken up by myeloid cells such as macrophages (32,33), dendritic cells (34), and neutrophils (35,36) and modulate their viability, migration, and function. This study addressed whether bisphosphonate-induced myeloid cell dysfunction might contribute to the pathological oral barrier immunity leading to the development of ONJ.…”
mentioning
confidence: 99%
“…The search for medications with the same therapeutic effectiveness as the BP (bisphosphonates) but with fewer side effects has resulted in the discovery of Denosumab, which is a human monoclonal antibody to the receptor activator of nuclear factor kappa-B that inhibits the development and activity of osteoclasts by blocking the binding of RANKL to RANK, decreasing bone resorption, and increasing bone density (1,2).…”
Section: Discussionmentioning
confidence: 99%
“…This antiresorptive agent is a human monoclonal antibody of nuclear factor kappa-B ligand (RANKL) that inhibits the development and activity of osteoclasts by blocking the binding of RANKL to RANK, decreasing bone resorption and increasing bone density (1)(2)(3).…”
Section: Introductionmentioning
confidence: 99%